APPLICATION OF DESIGN THINKING METHOD IN REDESIGNING THE UI/UX OF SIMAK (ACADEMIC INFORMATION SYSTEM) OF SRIWIJAYA UNIVERSITY BASED ON A MOBILE PLATFORM - Frans Juansyah; Dwi Rosa Indah (Fakultas Teknik Universitas Lambung Mangkurat, 2023)
Students at Sriwijaya University are having difficulty accessing academic information through SIMAK using their mobile devices due to a user interface that is not optimized for smartphones. In this study, the author used the Design Thinking method because it has stages that are very helpful in creating prototypes, such as the Empathize stage where the author can directly interact with users' personal opinions, up to the testing stage, which helps the author analyze the results of prototype creation so that further development can be more responsive and better. The prototype was tested through Maze, a platform that helps users test product or service prototypes quickly and efficiently. This platform is integrated with various prototype-making applications and allows users to collect qualitative and quantitative data in one place and the User Experience Questionnaire (UEQ) to analyze data from prototype testing. Based on the results of usability testing, the UEQ scores from 26 SIMAK users were above 1.6, with almost all assessment categories such as